2013
DOI: 10.1007/s10103-012-1258-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 810-nm low-level laser therapy on pain caused by orthodontic elastomeric separators

Abstract: The purpose of this study was to assess the effect of 810-nm (DMC Equipamentos, Sao Carlos, Brazil) continuous wave low-level laser therapy (LLLT) on the pain caused by orthodontic elastomeric separators. Thirty-seven orthodontic patients (12 male and 25 female, aged 11-32 years, mean age = 24.97 years) participated in the study, including 20 subjects aged 18 years or more, and 17 under 18 years of age. Four elastomeric separators (Dentarum, Springen, Germany) were placed for the first permanent molars (distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 46 publications
10
107
0
4
Order By: Relevance
“…A manual search for articles identified six more studies. Overall, 15 studies [1,6,8,9,14,15,[42][43][44][45][46][47][48][49][50] were selected for the analysis (Tables 1 and 2). Details of the search strategy are presented in Fig.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…A manual search for articles identified six more studies. Overall, 15 studies [1,6,8,9,14,15,[42][43][44][45][46][47][48][49][50] were selected for the analysis (Tables 1 and 2). Details of the search strategy are presented in Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…All studies included patients of both sexes. Eight studies applied the "split mouth" model as an experimental design [6,8,15,42,43,45,46,49] and in the others, researchers evaluated experimental groups in different subjects. Most of the studies included that they enrolled healthy patients with no systemic conditions.…”
Section: Characteristics Of the Included Studies Related To Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoblast and osteoclast differentiation, the expression of receptor activator of nuclear factor kappa ligand (RANKL)-and RANK-positive cells, and bone remodeling [12] were increased during orthodontic tooth movement, and collagen synthesis was stimulated [12,13] via the therapy. Furthermore, Bicakci et al [10] and Eslamian et al [14] found that LLLT was efficient in reducing orthodontic post-adjustment pain.…”
Section: Introductionmentioning
confidence: 97%
“…TENS and vibratory stimulation have been advocated for relieving orthodontic pain, but their effectiveness has never been proven . Although LLLT and chewing bite wafer or gum were shown to be useful for this purpose , controversies about the results caused a decline in their popularity.…”
Section: Introductionmentioning
confidence: 99%